Characterization of N-linked intact glycopeptide signatures of plasma IgGs from patients with prostate carcinoma and benign prostatic hyperplasia for diagnosis pre-stratification. Issue 15 (22nd June 2020) - Zhang, Yong; Lin, Tianhai; Zhao, Yang; Mao, Yonghong; Tao, Yiran; Huang, Yan; Wang, Shisheng; Hu, Liqiang; Cheng, Jingqiu; Yang, Hao
Abstract : The discovery of novel non-invasive biomarkers for discriminating between prostate carcinoma (PCa) patients and benign prostatic hyperplasia (BPH) patients is necessary to reduce the burden of biopsies, avoid overdiagnosis and improve quality of life. Abstract : The discovery of novel non-invasive biomarkers for discriminating between prostate carcinoma (PCa) patients and benign prostatic hyperplasia (BPH) patients is necessary to reduce the burden of biopsies, avoid overdiagnosis and improve quality of life. Previous studies suggest that abnormal glycosylation of immunoglobulin gamma molecules (IgGs) is strongly associated with immunological diseases and prostate diseases. Hence, characterizing N-linked intact glycopeptides of IgGs that correspond to the N -glycan structure with specific site information might enable a better understanding of the molecular pathogenesis and discovery of novel signatures in preoperative discrimination of BPH from PCa. In this study, we profiled N-linked intact glycopeptides of purified IgGs from 51 PCa patients and 45 BPH patients by our developed N -glycoproteomic method using hydrophilic interaction liquid chromatography enrichment coupled with high resolution LC-MS/MS. The quantitative analysis of the N-linked intact glycopeptides using pGlyco 2.0 and MaxQuant software provided quantitative information on plasma IgG subclass-specific and site-specific N -glycosylation. As a result, we found four aberrantly expressed N-linked intact glycopeptides across different IgG subclasses. In particular, the N -glycopeptide IgG2-GP09 (EEQFNSTFR (H5N5S1)) was dramatically elevated in plasma from PCa patients, compared with that in BPH patients (PCa/BPH ratio = 5.74, p = 0.001). Additionally, the variations in these N-linked intact glycopeptide abundances were not caused by the changes in the IgG concentrations. Furthermore, IgG2-GP09 displayed a more powerful prediction capability (auROC = 0.702) for distinguishing PCa from BPH than the clinical index t-PSA (auROC = 0.681) when used alone or in combination with other indicators (auROC = 0.853). In conclusion, these abnormally expressed N-linked intact glycopeptides have potential for non-invasive monitoring and pre-stratification of prostate diseases.